Addressing the Special Education Teacher Shortage in Central Kalimantan: Dynamics, Challenges, and Collaborative Governance Solution - Piter Joko Nugroho; Theo Jhoni Hartanto (AL-ISHLAH: Jurnal Pendidikan, 2026)
The shortage of Special Education Teachers (SET) relative to Students with Special Educational Needs (SEN) in Central Kalimantan Province remains a critical concern. The current SET–SEN ratio of 1:11, significantly below the national standard of 1:5, undermines equitable access to quality education for SEN students. This study examines the underlying dynamics and structural causes of this imbalance in public special schools (SLBN). A qualitative design was employed, with data collected through in-depth interviews, observations, and document analysis across selected SLBNs and relevant government institutions. Data were analyzed thematically, supported by source triangulation, member checking, audit trails, and peer debriefing to ensure rigor and credibility. The findings reveal that the SET shortage is a systemic and multidimensional issue driven by three interrelated factors: unsystematic, non–data-driven workforce planning; the absence of local undergraduate programs in special education; and limited interest among non-local applicants. These factors interact across policy, institutional, and individual levels, weakening the regional SET ecosystem. Peer debriefing further indicates that the issue reflects fragmented, cross-sectoral governance. Addressing the SET shortage requires a coordinated, collaborative governance approach. A four-stage framework—preparation, recruitment, placement, and continuous professional development (CPD)—is proposed to strengthen the SET ecosystem. Policy redesign that institutionalizes cross-sector collaboration is essential to ensure the sustainable and equitable fulfillment of SEN students’ educational rights.